Improving Critical Thinking and Problem-Solving Skills Through PBL: Evidence from Secondary Education - Rico Eko Andrianto; Taufiq Subhanul Qodr (Universitas Negeri Surabaya, 2025)
Critical thinking and problem-solving abilities are vital competencies of the 21st century; nevertheless, they have not yet been fully cultivated by traditional education methods. This study seeks to evaluate the impact of the Problem-Based Learning (PBL) model on the critical thinking skills and problem-solving abilities of junior high school students, while also comparing the outcomes with traditional instructional methods. The methodology employed was a quasi-experimental design featuring a non-equivalent control group, comprising 64 eighth-grade pupils allocated into experimental and control groups. The assessment tool was created utilizing Ennis indicators and Polya stages. The study results indicated that the experimental group exhibited substantial enhancements in both skills, evidenced by a modest N-Gain value (≈0.39) and a large effect size (Cohen's d > 1.0). Conversely, the control group exhibited merely a little increase. These findings reinforce the efficacy of PBL as a constructivist learning methodology that promotes active, collaborative, and reflective participation. The implication is that the systematic implementation of PBL can serve as an effective educational technique to enhance learning quality and prepare students with 21st-century competencies.